(untitled) (Perner’s Contacts, 2012)
Technical and technological progress affect the area of road freight transport. The age of vehicles is an indicator of "modernity", acceptability to the environment and competitiveness, as well as the state of road freight transport. The article deals with the analysis of the age structure and environmental friendliness of freight vehicles registered in the Slovak Republic.